Efektivitas kinerja pengawasan obat dan makanan di wilayah kerja Balai Besar Pengawas Obat dan Makanan di Bandung - Aristawidya, Levina; Zuhrotun , Ade (Journal of Pharmaceutical and Sciences, 2025)
The increasing demand for drugs and food will have an impact on the production and distribution of drugs and food which is increasingly widespread. The widespread distribution of drugs and food has caused public health problems related to quality and safety that do not meet standards, so that it is necessary to increase drug supervision both pre-market and post-market by the National Agency of Drug and Food Control (NADFC). Therefore, this article aims to determine the effectiveness of the monitoring performance of drug and food production and distribution facilities carried out by one of the Technical Implementation Units of Indonesia NADFC, namely Balai Besar POM in Bandung The method used in this article is descriptive qualitative using primary data from performance reports from the Balai Besar POM in Bandung from years 2020 to 2023. Based on the achievement of performance indicators, the implementation of supervision activities for drug and food production and distribution facilities by the POM Center in Bandung is considered quite effective as evidenced by the Performance Achievement Value which is always above 100% from year to year. The overall achievement value and performance efficiency from 2020 to 2023, respectively, include 104.66%; 101.38%; 107.60%; and 103.82%. However, if we look closely at the realization value per indicator each year, there are several indicators that have not reached the 2020-2024 strategic plan target so that further efforts are needed to improve and maximize the performance achievement value. These efforts can be successful if accompanied by collaboration and synergy of all stakeholders so that the public receives quality and safe drug and food products according to standards.